A preparation cycle in strength training as a form of health training for adults - MAŁGORZATA KAŁWA; TADEUSZ STEFANIAK; DARIUSZ HARMACIŃSKI; BARTOSZ GROFFIK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪The authors assume that 8-month systematic physical activity with individually selected resistance of progressively increasing volume and intensity will counteract the processes related to regress of motricity and the unfavourable change of body composition in people over 40 years old. Material and methods: ‪The research involved 178 persons (92 women and 86 men) aged 40-61 years old. The participants pursued training with small and medium weights, broken down into a younger (40-50 years) and an older (51-61 years) group. The workout plan was modelled on the adaptive strength training method (ASTM), which is used by weightlifters and bodybuilders. The change in overall physical fitness was assessed by means of the Pilicz test, body mobility and changes in selected parameters of body composition. Results: ‪In both groups (51-61 years old and 40-50 years old), a decrease in body weight and the adipose tissue and improved physical fitness and body mobility were noted. The most significant result was an increase by 18% of the lower limbs strength in women and men, while in the case of the upper limbs, the increase in strength in males was by 19% and in women by as much as 31%. Furthermore, levelling of overall fitness among the ASTM participants occurred. Conclusions: ‪Extensive mobilisation of the motor apparatus that is ensured by adaptive training offers highly beneficial effects in the fight against the symptoms of aging. After consultation with a doctor, this workout may be found useful in the prevention of injuries, the motor system dysfunctions, overweight and cardiovascular diseases in adults.